The big fear - Case, Andrew, 1971- (Thomas & Mercer, 2016)
When evidence that might clear veteran cop Ralph Mulino "disappears", Civilian investigator Leonard Mitchell forms an uneasy partnership with Mulino to uncover misconduct and corruption in the New York police force.